KOORDINASI HORIZONTAL KEGIATAN TNI MANUNGGAL MEMBANGUN DESA (TMMD) DI KELURAHAN BANGKA BELITUNG DARAT KECAMATAN PONTIANAK TENGGARA - Mandrawan Suseno (FISIP Universitas Tanjungpura, 2013)
This paper is motivated by the TNI Manunggal Village Building Management (TMMD) in the Village of Inland Pacific Islands Southeast Pontianak district has not implemented optimally, especially in the implementation of coordination between the District Military Command 1207/Ptk with the elements involved in activities TMMD. Based on these facts, this paper focuses on horizontal coordination of military activities TMMD in Bangka Belitung Aquatic Village District East Pontianak with aspects of coordination in Phase Planning. Preparation Phase, Implementation Phase and Phase Full Manunggal TMMD activities. The goal is to determine the horizontal coordination in the implementation of activities in the Village TMMD Pacific Islands Southeast Land District of Pontianak. The type of study is a qualitative research method deskreptif. The results showed that coordination in the planning stage has been carried out by elements of the leadership involved in activities TMMD, but has not followed through technical coordination between staff, with regard to budget support and targeting TMMD. Coordination in Preparation stage, especially in the administrative preparation has been done by the District Military Command 1207/Ptk the elements involved in activities TMMD, but coordination in the preparation of personnel to support TMMD not implemented optimally. Coordination in the Implementation Phase TMMD between Commander SSK TMMD with Headman, RW and RT in the Village of Bangka Belitung Army is not optimal, especially in community mobilization. Coordination in Phase Full Manunggal TMMD between the District Military Command 1207/Ptk Pontianak City Government has not am in an integrated and sustainable especially in maintenance activities TMMD results.Keywords: Horizontal Coordination, Planning Phase TMMD, Preparation Phase TMMD, Implementation Phase TMMD and phase complete cohesiveness TMMD